2009
DOI: 10.1007/s00284-009-9523-7
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Pathogenic Acanthamoeba Isolated from a Hospital in Brazil

Abstract: Studies on free-living amoebae (FLA), has been increased in recent years, especially related to the genus Acanthamoeba, because these organisms are widely found in the environment. The present work isolated and characterized this organism from biofilms and dust in hospital environment. 135 samples were collected in 15 different environments in a hospital at the south of Brazil. Thirty-one (23%) isolates were identified as morphologically belonging to the Acanthamoeba genus and 10 of these were submitted to tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 24 publications
3
32
2
Order By: Relevance
“…On the other hand, the prevalence of Acanthamoeba spp. in hospital dust samples from Brazil was reported to be 23% (19), which is lower than the present study. Variations in geographic conditions, climate, and health facilities affect the incidence of Acanthamoeba.…”
Section: Discussioncontrasting
confidence: 92%
“…On the other hand, the prevalence of Acanthamoeba spp. in hospital dust samples from Brazil was reported to be 23% (19), which is lower than the present study. Variations in geographic conditions, climate, and health facilities affect the incidence of Acanthamoeba.…”
Section: Discussioncontrasting
confidence: 92%
“…It was reported that Acanthamoeba spp. are more resistant to harsh conditions and can survive for a long time [34,35] . However, the variability of detection rates in several reports is due to variable seasonal temperature which affects the intensity and variety of Acanthamoeba spp.…”
Section: Discussionmentioning
confidence: 99%
“…Half of the Acanthamoeba isolates recovered from rivers, canals, and lakes in Arizona were A. lenticulata (41). A. lenticulata has also been isolated from biofilm samples collected from hospitals and swimming pools in Brazil (42,43) as well as soils and tap water samples in Florida (44). However, to our knowledge, the present study is the first examination of mycobacterial growth in A. lenticulata, with all other previous studies using species that belong to genotype T4: A. castellanii strains ATCC 30010 and ATCC 30234 or A. polyphaga LincAp-1 (10).…”
Section: Discussionmentioning
confidence: 99%